Regulatory B cells protect against chronic hypoxia‐induced pulmonary hypertension by modulating the Tfh/Tfr immune balance. Issue 4 (14th January 2023) - Li, Cheng; Liu, Pingping; Yao, Huiling; Zhu, Hao; Zhang, Shaoze; Meng, Fang; Li, San; Li, Guang; Peng, Yanping; Gu, Jing; Zhu, Liming; Jiang, Yongliang; et al.
Abstract: Hypoxia‐induced pulmonary hypertension (HPH) is a progressive and lethal disease characterized by the uncontrolled proliferation of pulmonary artery smooth muscle cells (PASMCs) and obstructive vascular remodelling. Previous research demonstrated that Breg cells were involved in the pathogenesis of pulmonary hypertension. This work aimed to evaluate the regulatory function of Breg cells in HPH. HPH mice model were established and induced by exposing to chronic hypoxia for 21 days. Mice with HPH were treated with anti‐CD22 or adoptive transferred of Breg cells. The coculture systems of Breg cells with CD4 + T cells and Breg cells with PASMCs in vitro were constructed. Lung pathology was evaluated by HE staining and immunofluorescence staining. The frequencies of Breg cells, Tfh cells and Tfr cells were analysed by flow cytometry. Serum IL‐21 and IL‐10 levels were determined by ELISA. Protein levels of Blimp‐1, Bcl‐6 and CTLA‐4 were determined by western blot and RT‐PCR. Proliferation rate of PASMCs was measured by EdU. Compared to the control group, mean PAP, RV/(LV + S) ratio, WA% and WT% were significantly increased in the model group. Anti‐CD22 exacerbated abnormal hemodynamics, pulmonary vascular remodelling and right ventricle hypertrophy in HPH, which ameliorated by adoptive transfer of Breg cells into HPH mice. The proportion of Breg cells on day 7 induced by chronic hypoxia was significantly higher than control group, which significantly decreased on day 14 and day 21. The percentage of Tfh cells was significantly increased, while percentage of Tfr cells was significantly decreased in HPH than those of control group. Anti‐CD22 treatment increased the percentage of Tfh cells and decreased the percentage of Tfr cells in HPH mice. However, Breg cells restrained the Tfh cells differentiation and expanded Tfr cells differentiation in vivo and in vitro. Additionally, Breg cells inhibited the proliferation of PASMCs under hypoxic condition in vitro. Collectively, these findings suggested that Breg cells may be a new therapeutic target for modulating the Tfh/Tfr immune balance in HPH. Abstract : Chronic hypoxia promoted Breg cells differentiation in the early stage of HPH, which significantly decreased in the late stage. Insufficient Breg cells exacerbated pulmonary vascular remodelling and dysregulated Tfh/Tfr cells in HPH. Adoptive transfer of Breg cells ameliorated pulmonary vascular remodelling and dysregulated Tfh/Tfr cells in HPH.